Strategi Dinas Koperasi dan Usaha Mikro Kabupaten Sidoarjo dalam Kinerja Koperasi melalui Bimbingan Teknis - Zakhilla, Faricha Septia Nur (Jurnal Pengabdian Kepada Masyarakat Sosial Humaniora, 2025)
The people's economy in Indonesia relies heavily on the role of cooperatives as a driving force for local economic development. In Sidoarjo Regency, the Cooperatives and Micro Enterprises Office implemented a cooperative strengthening strategy through targeted and applicable technical guidance (Bimtek). This Bimtek focused on improving the human resource capacity of cooperative administrators, strengthening governance, financial management, developing locally-based businesses, and utilizing digital technology. Data was collected through observation, documentation, and interviews with office staff and cooperative administrators. The results showed improvements in cooperative institutional performance, such as orderly financial reporting and regulatory compliance, supported by the digitalization of the reporting process. Obstacles such as budget constraints and low participation were successfully overcome through intensive mentoring and collaboration between various parties. These findings serve as evaluation material and recommendations for developing more effective and sustainable cooperative empowerment policies.